The impact of climate and water changes on the status of agriculture in Iraq - Zghair, Ansam Ali; Chandoul, Amara Saad (Journal of agricultural, environmental and veterinary sciences, 2020)
The researchers emphasize, in this paper, that the water crisis in Iraq and its serious economic and social problems, are mainly a problem of inequality in distribution of water and poor planning in its uses, rather than a natural crisis. Therefore, it has become imperative, with the help of qualified and specialized people, to offer an alternative that proves sustainability in distribution, storage, and water consumption, as possible and possible. In fact, the water wealth, as well as the arable lands, have not yet reached the peak of the potential, as all studies indicate the exploitation of between one fifth and a half of the total available. The eagerness to create crises and link the need to others is easier and useless, especially in the long run. The researchers adopted the descriptive approach, in addition to the analytical approach in reading and discussing data. The research concluded that the problems of agriculture are mainly related to three dimensions: natural, internal and regional. And that the means of solution are based on two pillars: the first, the need to think about adapting to climate change, and the second, the need to think wisely in dealing with the neighboring countries of Iraq, especially Iran and Turkey.